A música folclórica amazonense como um instrumento facilitador do ensino-aprendizagem de física no ensino médio - Farias, Rosa Suzana Batista (2011)
Teaching constitutes a major challenge for teachers today, especially for those who are traditionalists, and do not seek to adapt the lessons by existing means and methods that meet the needs of a professor in the twenty-first century. In order to build an enabler in the process of teaching and learning of physics content in high school, it was through alternative means of tools and a creative and motivating way to teach in an appropriate and supportive educational and pedagogical work. Through alternative means sought, within a vision of the arts, folk music enter the Amazon, as aid in the development of specific school subjects of physics, through investigation of the compositions of interpretive lyrics contextualizing nature which highlights the Amazon forests, rivers, lakes, forests, hunting and fishing than the legends and spells that are part of the culture of the region. The methodological guidelines were used in the research literature approach to descriptive and qualitativequantitative through action research, participatory form of dialectic